Mining and rock construction technology desk reference : rock mechanics, drilling and blasting, including acronyms, symbols, units and related terms from other disciplines /: rock mechanics, drilling and blasting, including acronyms, symbols, units and related terms from other disciplines. ([2010]) - Unknown
No abstract available